In Vitro Fertilization and Embryonic Development of Sargassum polycystum C. Agardh (Phaeophyceae) Under Different Salinity, pH, and Temperature Levels - Jeffersan G. Pada; Jayzon G. Bitacura (Science & Technology Asia, 2024)
Sargassum species are ecologically and economically important resources in marine environments. Recently, they have been subjected to mass cultivation to avoid overexploitation in the wild. Since physicochemical conditions could easily fluctuate in culture settings, this study evaluated the fertilization and embryonic development of Sargassum polycystum under various salinity, pH, and temperature levels. Reproductive organs were subjected to 30 ppt, 35 ppt, and 40 ppt salinity levels, 4.0-5.0, 5.5-6.5, and 7.5-8.5 pH ranges, and 29-30ºC, 34-35°C, and 39-40ºC temperature ranges. Results showed that fertilization and embryonic development of S. polycystum are significantly affected by the different treatments. Increased salinity (40 ppt), increased acidity (pH=4.0-5.0 & 5.5-6.5), and increased temperature (34-35°C & 39-40ºC) caused a significant decline in the fertilization and survival of embryos of S. polycystum. These results will be helpful for the development of better culture conditions for S. polycystum.